Segmentation procedures for the assessment of paranasal sinuses volumes. Issue 1 (February 2021) - Cellina, Michaela; Gibelli, Daniele; Cappella, Annalisa; Toluian, Tahereh; Pittino, Carlo Valenti; Carlo, Martinenghi; Oliva, Giancarlo
Background: The paranasal sinuses are complex anatomical structures, characterised by highly variable shape, morphology and size. With the introduction of multidetector scanners and the development of many post-processing possibilities, computed tomography became the gold standard technique to image the paranasal sinuses. Segmentation allows the extraction of metrical and shape data of these anatomical components that can be applied for diagnostic, education, surgical planning and simulation, and to plan minimally invasive interventions in otorhinolaryngology and neurosurgery. Discussion: Our aim was to provide a review of the existing literature on segmentation, its types and application, and the data obtained from this procedure. The literature search was conducted on PubMed (including Medline), ScienceDirect and Google Scholar databases, using the keywords as follows: 'paranasal sinuses', 'frontal sinus', 'maxillary sinus', 'sphenoid sinus', 'ethmoid sinus', in all possible combinations with the keywords 'segmentation' and 'volumetric analysis'. Inclusion criteria were: articles written in English, on living human subjects, on the adult population and focused on paranasal sinuses analysis. Conclusion: This article provides an overview of the types and main application of segmentation procedures on paranasal sinuses, and the results provided by the studies on this topic.